The Eye of the Needle. Education and inequalities between social justice, democracy and individualism at the beginning of the 21st century - Caligiuri, Mario (Formazione & insegnamento, 2018)
Nowadays, education can only partially build democracy and more importantly invest on social distances in the long term whereas new technologies encourage individualism not addressed to personal cultural investment but to unproductive participation. The latter is actually useless in the power relationships, since it produces illusions, considering that it consolidates and exasperates them. It is hard to understand what to pay attention for, therefore true power is the ability to know what to ignore. Finding solutions is not easy because it is like walking through the eye of a needle. It consequently needs to believe in quality education as a bulwark to an uncontrolled development. Here, artificial intelligence can be both an opportunity and an undeniable danger. It requires the possession of the appropriate language to describe and understand the reality in order to put education at the centre of the debate. It is an essential precondition of political and social strategies of the XXI century democracy.